Perilaku Identitas Kosmopolitan dalam Novel The Star and I Karya Ilana Tan - Cici Putri Ayati; Muhammad Adek (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Literary works are often seen as a reflection of society in the era in which and when the work was produced. The Star and I novel by Ilana Tan is a literary work that reflects the life of cosmopolitan society in the current era of globalization. Cosmopolitan identity has become an increasingly popular topic in the humanities and literature. This paper aims to analyze how cosmopolitan identity behavior is reflected in the novel The Star and I by Ilana Tan. This type of research is literary research using a qualitative approach and descriptive method. In this analysis, the novel The Star and I by Ilana Tan is chosen as the object of research because this novel describes a complex and pluralistic life that can reflect a cosmopolitan identity. The results of this study show how the concept of cosmopolitan identity is represented by the characters in the novel and how these characters interact with their environment. The results also show that cosmopolitan identity in the novel can be understood through characters who are able to navigate cultural differences and build relationships with people from different backgrounds. Cosmopolitan identity is also reflected in the way the characters articulate their thoughts, feelings and behaviors about identity and nationality. It is hoped that this paper can contribute to researchers and observers of literature in understanding how cosmopolitan identity is reflected in literary works and how literary works can play a role in promoting an understanding of cosmopolitanism in an increasingly globalized society.